The Northwestern Greenland Ice Sheet During The Early Pleistocene Was Similar To Today. Issue 1 (3rd January 2020) - Christ, Andrew J.; Bierman, Paul R.; Knutz, Paul C.; Corbett, Lee B.; Fosdick, Julie C.; Thomas, Elizabeth K.; Cowling, Owen C.; Hidy, Alan J.; Caffee, Marc W.
Abstract: The multi‐million year history of the Greenland Ice Sheet remains poorly known. Ice‐proximal glacial marine diamict provides a direct but discontinuous record of ice sheet behavior; it is underutilized as a climate archive. Here, we present a novel multiproxy analysis of an Early Pleistocene marine diamict from northwestern Greenland. Low cosmogenic nuclide concentrations indicate minimal near‐surface exposure, similar to modern terrestrial sediment. Detrital apatite (U‐Th‐Sm)/He (AHe) ages all predate glaciation by >150 million years, suggesting the northwestern Greenland Ice Sheet had, by 1.9 Ma, not yet incised fjords of sufficient depth to excavate grains with young AHe ages. The diamict contains terrestrial plant leaf wax, likely from land surfaces surrounding the ice sheet. These data indicate that a persistent, dynamic ice sheet existed in northwestern Greenland by 1.9 Ma and that diamict is a useful archive of ice sheet history and process. Plain Language Summary: The behavior of the Greenland Ice Sheet over the past several million years is poorly known. We analyzed 1.9 million‐year‐old sediment, deposited by glacial ice on the seafloor, to understand long‐term ice sheet history. Low cosmogenic isotope concentrations indicate persistent ice cover and at least meters of glacial erosion. Old apatite ages suggest deep glacial valleys had not yet been eroded. Leaf waxes produced by plants and algae indicate less than complete ice cover. By 1.9 million years ago, the Greenland Ice Sheet was a persistent, dynamic, erosive feature of Earth's climate and landscape. Key Points: By the Early Pleistocene, the northwestern Greenland Ice Sheet had removed preglacial soil and regolith but had not yet incised deep fjords Similar to today, ice‐free areas harbored vegetation that was incorporated into glacial marine sediment during ice advances Glacial marine diamict is an underutilized, but promising paleoclimate archive; existing archives should be re‐examined